Measles and immunological amnesia - Afrin, Sabrina; Mamun, Kazi Taib; Jannat, Hasnatul; Mahboob, Nabeela; Iqbal, Hasina (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Measles virus remains the most important cause of childhood mortality, causing a transient immunosuppression that accompanies and follows measles making the patients susceptible to secondary infections accounting for most of the measles-related complications and deaths. The majority of measles virus in the body uses Signaling Lymphocyte Activation Molecule (SLAM) as a receptor and only a minority of the virus may also use CD46. Infection and subsequent demise of SLAM cells may explain the severe immunosuppressive characteristic of this viral disease. Measles also reduce the nonspecific naïve B cells in the bone marrow, which fight unfamiliar infections and SLAM signaling intensifies CD95-mediated apoptosis of B cells. Furthermore, in experimentally infected non-human primates (NHPs) measles virus infects and depletes pre-existing memory lymphocytes, causing immune amnesia. Results from different studies explain the long-term immunologic sequelae of measles resulting in overall childhood infectious disease mortality. As measles infection is tightly coupled to measles-associated immune memory loss, advancement in research regarding post measles immunological amnesia is needed to investigate immune pathogenesis and host immune responses. J Bangladesh Coll Phys Surg 2020; 38(4): 191-196